Essays on the co-operatives’ performances in Malaysia / Azmah binti Othman - Othman, Azmah (2014)
Renowned for the potential in alleviating poverty, co-operative movement has been encouraged and supported by the government. This research investigates co-operative performances and efficiency in Malaysia using quantitative and qualitative methods. The first essay revealed that co-operatives’ role in economic development is still relevant. Credit and banking co-operatives had contributed to the movement’s growth and development. The National Co-operative Plans are important blueprint for co-operative development in the country. Investigation on factors influencing co-operative membership in the second essay revealed that membership is favourable to the older age groups as compared to younger age groups. Those working in government sector are more likely to be members. The duration of membership and frequency in annual general meeting attendance are found to be positively related to co-operative shareholding. An analysis on satisfaction and perception of co-operative performance showed that patrons are satisfied with the quality and reliability of goods and services. There are positive perceptions on the benefits of co-operation and on the role of co-operative in economic development and community wellbeing. Data Envelopment Analysis (DEA) of co-operative membership target groups in the third essay showed the co-operative groups’ efficiency score of 0.605 or equivalent to 65.3 percent inefficiency level in producing outputs. Co-operatives have operational “slacks” and inefficient resource usage. Tobit regression showed that turnover, equity and members are significant in influencing efficiency scores of co-operatives. Comparison of efficiency and productivity level of Bank Rakyat with conventional banks showed that Bank Rakyat was among the top five banks. Further analysis by including 5 other Islamic banks brought it to top six positions. The source of total factor productivity progress was technological progress while technical efficiency change remained stagnant. Tobit regression analysis revealed that loan intensity and assets were significant in determining the efficiency scores. Environmental factors are significant in influencing technological and scale efficiencies. Bank’s status (co-operative or Islamic) is significant in influencing technical and pure technical efficiency of banks. Action research in the last essay reviewed that co-operative establishment requires local communities involvement in decision-making process, human capabilities enhancement programmes, empowerment, entrepreneurial spirits, leadership qualities and local community commitments. Of the three community co-operatives in Marine Park Islands, Tioman achieved highest while Redang experienced moderate progress. Tinggi co-operative failed because lack of leadership, commitment and entrepreneurial spirits. Although co-operatives in Tioman and Redang have the potential to be the vehicle in alternative livelihoods strategy and social cohesion objectives, the co-operatives are faced with ample challenges. This research contributes towards an economic approach in performance evaluation of co-operatives in Malaysia. The high percentage of inefficient co-operatives revealed had provided empirical evidence that achievement of the Second National Co-operative Plan goals by 2015 will be affected. Results and recommendations from study are important for improvement of current co-operative management, policies, laws and regulations in Malaysia.